Perlindungan Hukum Bagi Pasien Usia Lanjut di Bidang Kesehatan dalam Perspektif Hak Asasi Manusia - Jaury Douglas Pardomuan; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The percentage of elderly people (seniors) in Indonesia is expected to continue to increase due to various factors, such as declining birth rates and improved life expectancy. Under these circumstances, the integration of seniors in development is crucial. Elderly individuals often experience health-related issues, and ideally, the state should be present to provide adequate health services for them. However, based on the research conducted, there are still many shortcomings in the legal framework to ensure the health and well-being of the elderly. Moreover, the de facto dissolution of the National Commission for the Elderly has created a gap in the entity directly responsible for advocating the development of a healthcare system for seniors. This study was conducted using the normative juridical method, with the main finding that legal reform is necessary to ensure that the current legal product, namely Law No. 13 of 1998 on Elderly Welfare, can be updated and Law No. 17 of 2023 should be revised to ensure better health and welfare for the elderly.